Contraceptive Efficacy and Safety of 52 mg LNG-IUS for up to Eight Years: Year 6 Data From the Mirena Extension Trial [OP04-1D]. (May 2020) - Jensen, Jeffrey T.; Kroll, Robin; Lynen, Richard F.; Schulze, Andrea; Lukkari-Lax, Eeva
Abstract : INTRODUCTION: The Mirena Extension Trial (MET) is a multicenter, open-label, single group study being conducted in the USA investigating contraceptive efficacy and safety of 52 mg LNG-IUS (Mirena®) during extended use for up to 8 years, with analyses planned at the end of Year 6, 7 and 8. METHODS: We recruited and screened current users of 52 mg LNG-IUS, ⩽35 years of age, after a minimum of 4 years and 6 months of use. Eligible consenting participants underwent a baseline visit 0 to 14 days before the end of Year 5. Institutional review board approval was obtained for all centers. The primary aim was to assess contraceptive efficacy (Pearl Index, PI) for up to 8 years of use. We present the results of the Year 6 analysis. RESULTS: Most of the 362 participants starting Year 6 completed and entered Year 7; 14 were lost to follow up and 40 discontinued. At baseline, 11.3% of women were between 18 and 25 years of age (mean=29.4 years [±3.1]). Around half (47.2%) were nulliparous. During Year 6, one pregnancy occurred for a Year 6 PI of 0.35 (CI 95% 0.01, 1.95). This pregnancy was of undetermined location, occurred with 52 mg LNG-IUS in situ and resolved without intervention. Overall, participants reported high levels of satisfaction (92.6% very satisfied, 6.4% somewhat satisfied). Treatment-emergent adverse events were reported in 166 patients, with 27 considered related to 52 mg LNG-IUS. CONCLUSION: 52 mg LNG-IUS maintains high contraceptive efficacy during Year 6 with a favorable safety profile. Satisfaction also remains high.